Redefinisi Ibadah pada Masa Pandemi Covid-19 - Eduward Purba; Dessy Handayani; Maria Magdalena; Nurnilam Sarumaha; Halim Wiryadinata (Sekolah Tinggi Teologi Berita Hidup, 2021)
AbstractThe reality of the emergence of the Covid-19 pandemic has changed the order of worship from on site to online, which has received many rejections. Pre-pandemic, worship was emphasized based on the dimensions of location (place). Therefore, this study aims to retrieve the true definition of worship. Through the library research, it gives the whole picture on the stage of evaluation of the worship itself. The results shows that worship actually transcends the dimensions of the location, devices, and tools used without hindering God's power for humans. Therefore, we bring back the definition of worship, both during and after COVID-19, to the real position that worship is the fellowship both during and after COVID-19 and to the real position that worship is the fellowship (body of Christ) of the relationship between God and humans regardless of the existing boundaries